OPTIMIZATION CONCENTRATION OF NATRIUM HIDROKSIDA IN 2.6-BIS-(3’,4’-DIMETHOXY-BENZYLIDENE)CYCLOHEXANONE SYNTHESIS THROUGH CLAISEN-SCHMID REACTION - Nurul Khotimah Putri Pertiwi; Sri Handayani; C Budimarwanti; Winarto Haryadi (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2015)
This research aimed at determining the optimization concentration of NaOH as a catalyst to produce the compound 2.6-bis(3’,4’-dimethoxybenzylidene) cyclohexanone in maximum yield through Claisen-Schmidt reaction. Synthesizing of 2.6-bis-(3’,4’ dimethoxybenzylidene)cyclohexanone through Claisen-Schmidt reaction was conducted by stirring method for two hours at 10°C. Raw materials used were 3,4-dimethoxybenzaldehyde and cyclohexanone. In this research, NaOH was used as a catalyst. The solvents that used were aquades and methanol. Moles variations of NaOH which was added in the research were 0.005; 0.01; 0.02; 0.04 and 0.08 moles. The results shows that the NaOH 0.005, 0.01, 0.02, 0.04, and 0.08 mol have produce in yield, 89.56, 81.23, 107.68, 115.98, and 14.55% respectively. From the data it can be seen the optimum yield obtained at NaOH 0.04 mol.